Faktor-faktor yang Mempengaruhi Keteraturan Pemeriksaan Antenatal Care di Puskesmas Biru-Biru Kabupaten Bone - Fatimah Fitriani Mujahidah (Sarana Ilmu Indonesia (salnesia), 2020)
One effective way to reduce morbidity and maternal mortality is to do antenatal checks. This study aims to determine the factors that influence the regularity of antenatal care examinations in health service units Bone Regency. The research design used in this study was cross sectional. The study population was 322 women who performed antenatal examination. Sampling 32 people selected by axal sampling. Research results show a significant relationship between knowledge (p value = 0,028) and regularity of antenatal visits with the attitude of Subjekts (p value = 0,01). Thus it can be concluded that there is a relationship between Subjekts knowledge and attitudes with regular K1-K4 antenatal visits and there is no relationship with husband’s suports with regular K1-K4 antenatal visits. This research recommends that health workers improve the counseling program for pregnant women, the need for the addition of medical deices to complete the need for antenatal checks at the puskesmas Biru-Biru Kabupaten Bone, and the need to increase awareness of family members, especially husbands,, to support pregnant women to examine their pregnancies as early as possible.